AYAT-AYAT SAINS DALAM AL-QUR’AN - Tajuddin, Muhammad; Mildawati, Titi; Masrifah, Rofiah (Jurnal Teknologi Pendidikan Madrasah, 2021)
Modern science of science is a connecting way to understand the Kauniyah verses about nature, therefore an understanding is needed to explain the meaning contained in the Kauniyah verses. This interpretation of the Qur'an will continue to develop along with the progress of science and science, this is the miraculous side of the Qur'an compared to other books where books other than the Qur'an only apply to certain people while al-Qur'an The Qur'an will continue to apply to all people until the end of time. This paper aims to find out what the Qur'an wants to convey through its Kauniyah verses. With the many verses related to nature, modern science has played a role in helping to explain the verses of His kauniyah that with science the Qur'an will be easier to understand. Keywords: Science, al-Qur'an